2014
DOI: 10.2989/16085914.2013.878241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flood variation on seasonal floodplain vegetation communities in the Okavango Delta, Botswana

Abstract: This study investigated the influence of flooding variation on floodplain vegetation in the Nxaraga Lagoon seasonal floodplains by sampling community composition and soil nutrient content in 1997, when flood levels were unusually low, and again in 2010 when flood levels were unusually high. In each of the eight vegetation zones identified in 1997, five plots were randomly selected. Flooding duration in each plot was estimated as the number of weeks in which the plots were inundated. Multi-response permutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Wild elephant samples collected in 2010 more commonly contained coccidian oocysts and fluke eggs than in other years, and fluke eggs were also more common than average in 2010 and 2011. Flood levels in the Delta were unusually high in 2010 ( Tsheboeng et al., 2014 ), and this could have favoured parasite transmission through, variously and non-exclusively, more humid soil supporting parasite development and survival, better conditions for snail intermediate hosts of fluke, and higher host population density as a result of lower available land area. A more persistent effect might be expected for fluke than for intestinal coccidia, since flukes are generally longer-lived parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Wild elephant samples collected in 2010 more commonly contained coccidian oocysts and fluke eggs than in other years, and fluke eggs were also more common than average in 2010 and 2011. Flood levels in the Delta were unusually high in 2010 ( Tsheboeng et al., 2014 ), and this could have favoured parasite transmission through, variously and non-exclusively, more humid soil supporting parasite development and survival, better conditions for snail intermediate hosts of fluke, and higher host population density as a result of lower available land area. A more persistent effect might be expected for fluke than for intestinal coccidia, since flukes are generally longer-lived parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of soil nutrient content between years 2010 and 1997 was done through re-sampling soil from zones sampled during low flood 13 selected on the basis of homogenous vegetation cover along an elevation gradient between a river channel (low) and dry land (high) , and Sporobolus spicatus and Sporobolus acinifolius (Zone 8). 19 Zones 1 and 2 were located in the primary floodplains which are closer to the river channel while Zones 3, 4, 5, 6 and 7 were located in secondary floodplains on relatively intermediately elevated areas. Zone 8 was found in the tertiary floodplains, which are relatively highly elevated areas.…”
Section: Soil Samplingmentioning
confidence: 92%
“…Previous studies in the Okavango Delta such as Tsheboeng et al (2014), Murray-Hudson et al (2006), McCarthy et al (2005, Bonyongo (1999) and Ellery et al (1993) have demonstrated that vegetation communities are influenced by flood duration, depth and frequency. In flood recession farming areas of the Okavango Delta, weed species composition and diversity were found to be influenced by frequency of cultivation, suggesting that cultivation frequency can be an important driver of weed species assemblages in flood recession farming.…”
Section: Discussionmentioning
confidence: 93%
“…Handa et al (2012) showed that facultative upland weeds completely dominated the drained cultivated sites as opposed to permanently inundated areas dominated by either obligate or facultative wetland species. Similarly, in the Okavango Delta, Setaria sphacelata was found to be more pronounced in areas subjected to shallow flooding (Bonyongo 1999) while Eleocharis dulcis and Leersia hexandra were found to be facultative wetland species as they were more tolerant to prolonged flooding (Tsheboeng et al 2014). These studies were focused on the floodplains, and no vegetation studies to date have been done in molapo farming.…”
Section: Introductionmentioning
confidence: 99%